ANALYSIS OF THE EFFECT OF THIRD-PARTY FUNDS FOR MURABAHAH, CAPITAL ADEQUACY RATIO (CAR), AND NON-PERFORMING FINANCING (NPF) MURABAHAH TO RETURN ON ASSETS (ROA) AT ISLAMIC COMMERCIAL BANKS IN INDONESIA FOR THE 2017-2020 PERIOD - Ropi Marlina; Juliani Lisma Sari; Dewindi Dewindi; Novian Mardani; Ade Nurhayati (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2023)
The purpose of this study is to analyze the Effect of Third-Party Funds (DPK), Capital Adequacy Ratio (CAR), and Murabahah Non-Performing Financing (NPF) on Return on Asset (ROA). The research method used is in this study is a descriptive method with a quantitative approach and uses panel data regression analysis (Time Series and Cross Series) with a Fixed Effect Model (FEM) model using Eviews software version 10. The sampling method used is purposive sampling, which uses several criteria so that there are 12 Islamic Commercial Banks that are used as samples operating in Indonesia and registered with the OJK from 2017-2020. The results showed that the Third-Party Fund Variable (DPK) and Capital Adequacy Ratio (CAR) had a positive and significant effect on Return on Asset (ROA) in Islamic Commercial Banks. Murabahah's Non-Performing Financing (NPF) has a negative and insignificant influence on Return on Asset (ROA). Murabahah's Third Party Funds, Capital Adequacy Ratio (CAR), and Murabahah's Non-Performing Financing (NPF) simultaneously (together) have a positive and significant influence on Return on Asset (ROA). Islamic commercial banks must consider various solutions to obtain high profitability. Murabahah's Third Party Funds, Capital Adequacy Ratio (CAR), and Murabahah's Non-Performing Financing (NPF) must be maintained and tiered to obtain maximum profitability.